Pulsed electric field (PEF) as an intensification pretreatment for greener solvent lipid extraction from microalgae. (4th February 2013) - Zbinden, Mauricio D. Antezana; Sturm, Belinda S.M.; Nord, Ryan D.; Carey, William J.; Moore, David; Shinogle, Heather; Stagg‐Williams, Susan M.
Abstract Microalgae, with their high lipid content, are a promising feedstock for renewable fuels. Traditionally, human and environmentally toxic solvents have been used to extract these lipids, diminishing the sustainability of this process. Herein, pulsed electric field technology was utilized as a process intensification strategy to enhance lipid extraction from Ankistrodesmus falcatus wet biomass using the green solvent, ethyl acetate. The extraction efficiency for ethyl acetate without PEF was lower (83–88%) than chloroform. In addition, the ethyl acetate exhibited a 2‐h induction period, while the chloroform showed no time dependence. Utilizing PEF technology resulted in 90% of the cells being lysed and a significant enhancement in the rate of lipid recovery using ethyl acetate. The increase in lipid recovery was due to the presence of the electric field and not due to temperature effects. The PEF technology uses less energy than other PEF systems reported in the literature. Biotechnol. Bioeng. 2013; 110: 1605–1615. © 2013 Wiley Periodicals, Inc.